Overexpression of DgWRKY4 Enhances Salt Tolerance in Chrysanthemum Seedlings - Wang, Ke; Wu, Yin-Huan; Tian, Xiao-Qin; Bai, Zhen-Yu; Liang, Qian-Yu; Liu, Qing-Lin; Pan, Yuan-Zhi; Zhang, Lei; Jiang, Bei-Bei (Frontiers in Plant Science, 2017)
High salinity seriously affects the production of chrysanthemum, so improving the salt tolerance of chrysanthemum becomes the focus and purpose of our research. The WRKY transcription factor (TF) family is highly associated with a number of processes of abiotic stress responses. We isolated DgWRKY4 from Dendranthema grandiflorum, and a protein encoded by this new gene contains two highly conserved WRKY domains and two C2H2 zinc-finger motifs. Then, we functionally characterized that DgWRKY4 was induced by salt, and DgWRKY4-overexpression in chrysanthemum resulted in increased tolerance to high salt stress compared to wild-type (WT). Under salt stress, the transgenic chrysanthemum accumulated less malondialdehyde (MDA), hydrogen peroxide (H2O2) and superoxide anion (O2-) than WT, accompanied by more proline, soluble sugar and activities of antioxidant enzymes than WT; in addition, a stronger photosynthetic capacity and a series of up-regulated stress-related genes were also found in transgenic chrysanthemum. All results demonstrated that DgWRKY4 is a positive regulatory gene responding to salt stress, via advancing photosynthetic capacity, promoting the operation of ROS-scavenging system, maintaining membrane stability, enhancing the osmotic adjustment, and up-regulating transcript levels of stress-related genes. So DgWRKY4 can serve as a new candidate gene for salt-tolerant plant breeding.